2015
DOI: 10.1097/nna.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Research Capacity and Use of Evidence in Acute Care

Abstract: Findings continue to demonstrate the need for new approaches to reduce the research-practice gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Other notable similarities with this study and findings reported in the literature are the demonstrated statistical differences by nursing degree, certification, and nurses' roles, indicating that nurses in leadership or support roles with higher degrees (baccalaureate or graduate degrees) and certification had more positive attitudes toward implementation (Duffy et al, 2015;Melnyk et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Other notable similarities with this study and findings reported in the literature are the demonstrated statistical differences by nursing degree, certification, and nurses' roles, indicating that nurses in leadership or support roles with higher degrees (baccalaureate or graduate degrees) and certification had more positive attitudes toward implementation (Duffy et al, 2015;Melnyk et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, Reynolds et al [51] reported that significant improvement in nursing knowledge was noted among nurses of the neurological problems and other assessment subscale score as well as the total stroke knowledge assessment score post guidelines. In addition to Duffy et al [52] who mentioned that after receiving educational program about stroke, nurses gained knowledge about assessments and importance of follow-up program for patients. Moreover, Han and Chen [53] mentioned that the majority of nurses recognize hypertension as a risk factor for stroke, whereas awareness about other common risk factors as unhealthy lifestyle including smoking and lack of exercise as a risk factor for stroke was low.…”
Section: Discussionmentioning
confidence: 99%
“…[12,25] (2) Create a vibrant research culture, environment, and infrastructure. [5,12,23] (3) Secure funding.…”
Section: Discussionmentioning
confidence: 99%